Time variation of bed deformation near bridge piers - Shen, Hsieh Wen, author; Agawa, Yoshiaki, author; Karaki, Susumu S., author (Colorado State University. Libraries, 1965)
Time variation of scour depth at a circular pier is described in the paper. Adequate design of bridge pier foundation requires proper assessment of this phenomena. The deepest point of scour at any time occurred at the front of the pier, and thus analysis was made for flow in the stagnation plane upstream of the pier. Idealized experimental studies were performed to aid the analysis. Experiments indicated that Froude number was the most important factor in determining scour depth. With known or assumed values of velocity and flow depth, scour dept h can be determined for any time.
CEDR65HWS-YO-SK1.
Presented at the International Association for Hydraulic Research, Eleventh International Congress, Leningrad, 1965.
Keywords: Scour at bridges; Piers